The Role of Thromboinflammation in Delayed Cerebral Ischemia after Subarachnoid Hemorrhage - McBride, Devin W.; Blackburn, Spiros L.; Peeyush, Kumar T; Matsumura, Kanako; Zhang, John H. (Frontiers in Neurology, 2017)
Delayed cerebral ischemia (DCI) is a major determinant of patient outcome following aneurysmal subarachnoid hemorrhage. Although the exact mechanisms leading to DCI are not fully known, inflammation, cerebral vasospasm, and microthrombi may all function together to mediate the onset of DCI. Indeed, inflammation is tightly linked with activation of coagulation and microthrombi formation. Thromboinflammation is the intersection at which inflammation and thrombosis regulate one another in a feedforward manner, potentiating the formation of thrombi and pro-inflammatory signaling. In this review, we will explore the role(s) of inflammation and microthrombi in subarachnoid hemorrhage (SAH) pathophysiology and DCI, and discuss the potential of targeting thromboinflammation to prevent DCI after SAH.